Decline in head circumference growth and associated factors in congenital Zika syndrome - Eliana Harumi Morioka Takahasi; Maria Teresa Seabra Soares de Britto e Alves; Marizélia Rodrigues Costa Ribeiro; Alcione Miranda dos Santos; Marcos Adriano Garcia Campos; Vanda Maria Ferreira Simões; Gláucio Andrade Amaral; Patrícia da Silva Sousa; Demócrito de Barros Miranda-Filho; Antônio Augusto Moura da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
Little is known about the evolution of head circumference (HC) in children with congenital Zika syndrome (CZS). This study aims to evaluate HC growth in children with CZS in the first three years of life and identify associated factors. HC data obtained at birth and in neuropediatric consultations from 74 children with CZS were collected from the Child's Health Handbook, parents' reports, and medical records. Predictors of HC z-score were investigated using different mixed-effects models; Akaike's information criterion was used for model selection. The HC z-score decreased from -2.7 ± 1.6 at birth to -5.5 ± 2.2 at 3 months of age, remaining relatively stable thereafter. In the selected adjusted model, the presence of severe brain parenchymal atrophy and maternal symptoms of infection in the first trimester of pregnancy were associated with a more pronounced reduction in the HC z-score in the first three years of life. The decrease of HC z-score in CZS children over the first three months demonstrated a reduced potential for growth and development of the central nervous system of these children. The prognosis of head growth in the first 3 years of life is worse when maternal infection occurs in the first gestational trimester and in children who have severe brain parenchymal atrophy.